O avesso da lógica: aspectos da relação ensino aprendizagem na escola Tia Ciata - Castro, Monica Rabello de (1990)
This study ains to ask some questions about the 'School Failure' in a specific group of students of the Public System in Rio de Janeiro. Based on a transdisciplinary approach some classes ocurrences were analysed. The basic material is the dialogue betwe~n teachers and pupils of the Escqla Tia Ciata. The possibility of a dialogistic relationship through the individuaIs speaching was searched. The Escola Tia Ciata had some singular characteristics as related to its population as to its methodology. Its goal would be to assist adolecents that had been excluded from Public Schools because they had overshot the age to be literated or had had inadequate behavior as compared to normal standars. They bear the stigma of marginalization and are named 'pivetes', 'meninos de rua', 'menores', 'favelados', etc. estreet boys). Part of the data here presented resolted from the following scholar pedagogycal proposition: the finding of the theme's interdisciplinaryty through the investigation of the boy's life story. The procedures were discussed by the School staff till last 80's. The study envolves 69 subjects from 12 to 18 years old besides their 7 professors. The conclusion·are limited to the context but may be a background to other similar works.